Methodological and linguistic aspects of Peruvian appellation of origin research - Arana Courrejoulles, Carmen (1999)
The concept of appellations of origin is contemplated within the Industrial Property Law D.L Nº823, Art. 219, which states: "An appellation of origin shall be understood as that which uses the name of a region or geographical place of the country that serves to designate a product originating therein and whose quality or characteristics are due exclusively or essentially to the natural and human factors of the place".